The Influence of Organizational Culture, Leadership Style, and Learning Motivation on Student’s Performance of Faculty of Education and Teacher Training at Universitas Jambi - Aulia, Ghea Ratu; Nainggolan, Cindi Nurlela; Yuliani, Adelia; Yusuf, Muhammad; A. Niduaza, Angela (Educational Leadership and Management Journal, 2025)
One of the things that decides how productive a company is its culture. Organizational success, both overall and in terms of individual performance inside a given company, is strongly correlated with the caliber of leadership present. Workers with a strong desire to succeed will give their all on the job, helping the business reach its goals. Throughout its existence, a company or organization relies on service quality to help it reach its full potential, allowing it to compete, or at least stay up with, the fast-paced commercial world. The researchers set out to determine how factors including leadership style, corporate culture, and employee motivation affect the quality of services provided to college students. Using both primary and secondary sources, this study ran from September to October. Participants in this research were undergraduates from the College of Management, the College of Teacher Training and Education, and the College of Agricultural Sciences who were enrolled in the first through eighth semesters of the 2018–2024 school year. The three universities used the proportionate random sampling technique to collect student samples. Observation and interviews are used to gather data. When processing data, tabulations and percentages are used. A multiple regression analysis is used. The study's findings highlight the importance of leadership, motivation, and organizational culture in shaping service quality. Keywords: Organizational culture; leadership; motivation.